Modulation of the rat intestinal microbiota in the course of Anisakis pegreffii infection - Zeng, Min-hao; Li, Shan; Lv, Qing-bo; Wang, Xiao-xu; Qadeer, Abdul; Mahmoud, Mohamed H. (Frontiers in Veterinary Science, 2024)
Background: Anisakis are globally distributed, marine parasitic nematodes that can cause human health problems, including symptoms such as vomiting, acute diarrhea, and allergic reactions. As parasitic nematodes that primarily affect the patient's digestive tract, intestinal helminths can interact directly with the host microbiota through physical contact, chemicals, or nutrient competition. It is widely accepted that the host microbiota plays a crucial role in the regulation of immunity.Materials and methods: Nematodes collected from the abdominal cavity of marine fish were identified by molecular biology and live worms were artificially infected in rats. Infection was determined by indirect ELISA based on rat serum and worm extraction. Feces were collected for 16S rDNA-based analysis of microbiota diversity.Results: Molecular biology identification based on ITS sequences identified the collected nematodes as A. pegreffii. The success of the artificial infection was determined by indirect ELISA based on serum and worm extraction from artificially infected rats. Microbiota diversity analysis showed that a total of 773 ASVs were generated, and PCoA showed that the infected group was differentiated from the control group. The control group contained five characterized genera (Prevotellaceae NK3B31 group, Turicibacter, Clostridium sensu stricto 1, Candidatus Stoquefichus, Lachnospira) and the infected group contained nine characterized genera (Rodentibacter, Christensenella, Dubosiella, Streptococcus, Anaeroplasma, Lactococcus, Papillibacter, Desulfovibrio, Roseburia). Based on the Wilcoxon test, four processes were found to be significant: bacterial secretion system, bacterial invasion of epithelial cells, bacterial chemotaxis, and ABC transporters.This study is the first to analyze the diversity of the intestinal microbiota of rats infected with A. pegreffii and to determine the damage and regulation of metabolism and immunity caused by the infection in the rat gut. The findings provide a basis for further research on host-helminth-microbe correlationships.